Effect of pegagan (Centella asiatica) nanoparticle coated with chitosan on the cytokine profile of chronic diabetic mice - Muchtaromah, Bayyinatul; Firdaus, Ana MK.; Ansori, Arif NM.; Duhita, Maharani R.; Minarno, Eko B.; Hayati, Alfiah; Ahmad, Mujahidin; Analisa, Izza (Narra J, 2024)
Diabetes is closely related to immune response problems when it occurs chronically. Pegagan (Centella asiatica) is a medicinal plant with active compounds. Madecassoside is beneficial in treating diabetes, and nanoparticle technology is expected to enhance the medicinal potential and availability of pegagan compounds. The aim of this study was to determine the effect of chitosan-coated pegagan nanoparticles on the cytokine profile of chronic diabetic mice, which included CD4+TNF-α+, CD8+TNF-α+, CD4+IFN-γ+, CD8+IFN-γ+ and IL-6+. An experimental study with a randomized complete block design (CRD) consisting of six treatments with seven replicates was conducted. The groups were: healthy mice as negative control; diabetic mice treated with distilled water as positive control and diabetic mice treated with nanoparticle coated with chitosan (NPC) 20 mg/kg, 30 mg/kg, 40 mg/kg, and metformin 130 mg/kgBW. The data were tested using one-way analysis of variance (ANOVA) with a significance level of 5% and continued with the Duncan’s multiple range test. The results showed that pegagan NPC could significantly reduce the relative number of CD4+TNF-α+, CD8+TNF-α+, CD4+IFN-γ+ and CD8+IFN-γ+ and IL-6 in the dose of 20 mg/kg, 30 mg/kg and 40 mg/kg (p<0.05). The treatment dose of 20 mg/kg reduced CD4+TNF-α+, CD8+TNF-α+, CD4+IFN-γ+, CD8+IFN-γ+ to the levels of healthy mice and a dose of 30 mg/kg could reduce IL-6 as in healthy mice. These findings suggest that chitosan-coated pegagan nanoparticles are a promising therapy for diabetes, as they have the potential to modulate the immune response associated with chronic diabetes.